Improving Pregnancy Tactics at Risk of Premature Birth (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
There is no clear understanding of which microbes are normal for the human microbiome [1]. The Human Microbiome Project (IMP) has done a lot of research to define the concept of a microbiome that is considered normal for humans, and the concept of "Normal Microbiome" is every concluded that it is individual for one organism [2]. Sub-Saharan Africa faces serious challenges in maternal and infant health. In 2017, 66% of all maternal deaths worldwide occurred in sub-Saharan Africa [33], and in 2020 there were 50 infant deaths per 1,000 live births [34]. Many of these adverse birth outcomes are caused by preventable or treatable infectious diseases. HIV accounts for 24–50% of pregnancy-related deaths in high-prevalence areas and is the leading cause of death among cisgender women of reproductive age [3, 4]. The risk of HIV infection increases during pregnancy and the postpartum period, which increases the risk of vertical transmission [5]. Pregnancy is a normal physiological state that affects the composition of the vaginal microbiome. During pregnancy, there is a gradual increase in lactobacillus species (including L. iners) and a decrease in microbial diversity, followed by a rapid increase in the diversity and anaerobic species in the postpartum period [6, 7, 8, 9, 10,11]. This is mediated by estrogen, which promotes the accumulation of glycogen in the vaginal epithelium and supports the growth of lactobacilli [11, 12]. Given the relationship between Lactobacillus abundance and an optimal microbiome, studies have shown that pregnancy induces favorable changes in the microbiome to prevent maternal genital infections and adverse birth outcomes [7]. In contrast, there is a rapid increase in bacterial diversity during the postpartum period [10, 11]. Premature birth is more than 10% worldwide. There are significant disparities in the frequency of preterm birth between countries' populations. Worldwide, approximately 15 million pregnancies occur at less than 37 weeks of gestation each year [13]. Preterm birth (PB) remains the second most common cause of neonatal death worldwide and the most common cause of infant mortality in middle- and high-income countries [14]. The consequences of PB persist from early childhood through adolescence and adulthood [15,16].